2022
DOI: 10.7759/cureus.23733
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Rectal Ulcer Syndrome Mimicking Perianal Crohn's Disease

Abstract: Solitary rectal ulcer syndrome (SRUS) is an uncommon condition that presents with non-specific symptoms shared by other disease processes. This case report shares a unique presentation in which a patient was thought to have fistulous perianal Crohn's disease then underwent treatment with infliximab but was ultimately found to have SRUS. The prognosis and treatment of SRUS vary greatly from inflammatory bowel disease. Making the correct diagnosis is imperative when considering Crohn's disease and its mimickers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“… 1 The incidence of SRUS is reported to be around 1 case per 100 000 persons every year, but it is believed to be underreported. 2 , 3 The symptoms include a sanguineous rectal discharge, the passage of mucus, and an uncomfortable feeling of inadequate evacuation of stool. 4 It has been reported that any injury in the mucous lining of rectum and localized ischemia are causes.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The incidence of SRUS is reported to be around 1 case per 100 000 persons every year, but it is believed to be underreported. 2 , 3 The symptoms include a sanguineous rectal discharge, the passage of mucus, and an uncomfortable feeling of inadequate evacuation of stool. 4 It has been reported that any injury in the mucous lining of rectum and localized ischemia are causes.…”
Section: Introductionmentioning
confidence: 99%